Pengukuran Kadar Aseton Udara Nafas sebagai lndikator Peningkatan Ketogenesis pada Penderita Diabetes Melitus Tidak Terkontrol - Moh. Robikhul Ikhsan; Luthfan Budi Purnomo; Mitrayana Mitrayana (Faculty of Medicine, Universitas Islam Indonesia, 2010)
Impaired of carbohydrate metabolism is characteristic of Diabetes Mellitus (OM) subjects that cause dysregulation of glucose uptake by target cell. Ketogenesis is compensation of this condition. The basic of this process is fatty acid oxydation. Increasing of fatty acid oxydation formed ketone bodies that we called acetone and can detected by air breathing. Aim of study to determine corelation between acetone level in air breath test as indicator of fatty acid oxydation and fasting blood glucose level in uncontrolled OM subjects.Cross-sectional, uncontrolled OM subjects and healthy person as control group. We measured fasting blood glucose (FBG) level and samples of air breath and analyse with spectroscopy fotoacustic laser. Corelation betwen level of acetone and FBG analyse with Pearson corelation. Compare means of acetone level between OM subject and control group analyse with non parametric mann-whitney U test. P value 0,05, Cl 95%. Ten uncontrolled OM subjects and 10 healthy persons as control group was followed this study. Mean of age and body mass index are 48,7 2: 5,6 vs. 49,2 2: 4,4 years (p>0,05 IK 95%) and BMI 22,4 2: 2,1 vs. 22,9 2: 3,8 kg!m2 (p>0,05 IK 95%). Level of acetone between OM subjects and control group 260.:!: 41,1 vs 177.:!: 18,4 ppm (p<0,05). There is strong corelation between acetone level and FBG level (r=0,97 p<0,05) Strong corelation between acetone level in air breath with FBG level. We can assumed that level of acetone in air breath can use as indicator of increasing ketogenesis in uncontrooled OM subjects.